Rethinking the integration of ICT in education: Towards a communication model to promote sustainable development - Machkour Mounia; Lamalif Latifa; Faris Sophia; Mansouri Khalifa; Akef Fatiha (E3S Web of Conferences)
The aim of this study is to reflect on how to integrate ICT (Information and Communication Technologies) into education, adopting an approach that promotes sustainable development through interaction and communication between educational players. The study aims to identify the most effective communication strategies for better integrating ICT into the learning process. Since communication fosters the exchange of ideas on innovative pedagogical practices. This research presents an analysis of trends, gaps and perspectives around sustainable education, focusing on communication and the implementation of educational technologies. The study proposes a new conceptual framework for organizing information sharing between the various players in education. This model places a strong emphasis on how interactions between different actors can contribute to education for sustainable development. The proposed model is a theoretical advance that could guide future research on improving the process of ICT integration and promoting high-quality education.